Power Monitoring System using the Internet of Things for Photovoltaic Powered Fertigation System - Ahmad Safawi, Noor Syahirah; Mohamad Nor, Ahmad Fateh (Emerging Advances in Integrated Technology, 2023)
This research paper explains the concept of photovoltaic (PV) systems. Among renewable energy technologies, PV systems rank third after hydropower and wind in terms of usage. They find significant application in agricultural activities, contributing to income generation for daily livelihoods. However, certain plant species demand meticulous attention to achieve optimal efficiency, necessitating a larger workforce for their care. By incorporating the Internet of Things (IoT), users gain the ability to remotely monitor PV system performance through a dedicated application. The central goal of this project involves crafting a simulation of an IoT system. This system is intended for monitoring the functionality of PV systems and devising an IoT-based model for overseeing the power aspects of PV systems in conjunction with fertigation systems (watering plants with nutrient solutions). A key feature of this system is its capacity to gauge the IoT model’s effectiveness by contrasting outcomes derived from hands-on observation and simulated scenarios. The outcomes of this study reveal that the developed IoT system effectively tracks real-time parameters like current, voltage, generated power, and solar PV temperature. It successfully establishes a link between users and the IoT infrastructure for system monitoring. Looking ahead, the gathered PV output data will be instantly accessible on mobile devices. This empowers users to assess the performance of their PV systems concerning fertigation.